SURVIVAL ANALYSIS OF CONTINUOUS AMBULATORY PERITONEAL DIALYSIS ON PATIENTS WITH END STAGE RENAL DISEASE IN SARDJITO HOSPITAL PERIOD 2007-2011 - Kohar, Moch. Abdul; Danarto, H R (Indonesian Urological Association, 2018)
Objective: This study was aimed to analyze the survival rate on End Stage Renal Disease (ESRD) patients and underwent Continuous Ambulatory Peritoneal Dialysis (CAPD) insertion surgery. Materials & Methods: The subjects of this study were 58 people diagnosed as chronic renal failure and underwent CAPD insertion surgery. This type of research is retrospective, using medical record data in Sardjito Hospital, and then we performed patient survival analysis with CAPD procedure performed on end stage renal disease patient. Results: In survival test performed on patients who underwent CAPD insertion without considering other factors, the mean survival rate was 40.26 months. Kaplan Meier curve obtained 3 and 5 years survival rate of 62% and 45% respectively. Furthermore, the survival test is done by dividing into two group diabetes mellitus (DM) and non-diabetes mellitus (non-DM). In CAPD-attached patients with DM, has a lower mean survival time compared to non-DM. Mean survival time of CAPD patients with comorbid of DM 36.05 months while non-DM 43.43 months. In this study, the Hazard Ratio was 1.44 (0.69-2.99) DM: Non DM. In the survival test by dividing into two age groups, age group ≥ 55 years and <55 years. The results obtained mean survival time for age group ≥ 55 years 36.02 months and for age group <55 years 43.08 months. Conclusion: Patients with kidney failure who underwent CAPD with comorbid DM had lower survival compared with non-DM. The younger the age of the patient that underwent CAPD insertion, the survival rate increase.